Effect of sowing dates on the vegetative growth and yield parameters of two quinoa (Chenopodium quinoa Willd.) genotypes - Smail Mehda; Mabrouka Oustani; Sana Bouazza; Imane Djaballah (Journal of Agriculture and Applied Biology, 2023)
The aim of the present study was to select the best sowing time for two quinoa genotypes (Chenopodium quinoa Willd) grown in Ouargla, located in the Saharan region of Algeria. The adopted experimental device is of the random block type, comparing the effect of three sowing dates in 2018: October 16th, October 31st, and November 15th, on some vegetative growth parameters (number of seedlings raised, total number of plants, total fresh weight of plants, height of plants at panicle stage, number of branches per plant, average weight per plant), and yield parameters (number of panicles per plant, weight of the main panicle, weight of 1000 grains, and total weight of grains per square meter) of two quinoa genotypes: "Q102" Amarilla saccaca and "Giza". The obtained results show that the best sowing date for the "Q102" genotype is the first date (October 16th), which ranked first for most of the parameters studied. On the other hand, the best grain yield was observed by the second sowing date (October 31st). As for the "Giza1" genotype, no yield was observed for the first and second sowing dates, while a very low grain yield was observed only by the third sowing date. The results obtained make it possible to conclude the strong capacity of adaptation of genotype "Q102" to the edapho-climatic conditions of the south of Algeria compared to genotype "Giza1". In fact, this study shows that the production potential of quinoa in the Saharan regions is linked to both the genotype and the sowing date.